On Sahastata (Araneae: Filistatidae): complementary description of the generotype and two new species from Oman and Morocco - Magalhaes, Ivan L. F.; Stockmann, Mark; Marusik, Yuri M.; Zonstein, Sergei L. (Zootaxa, 2020)
The Filistatinae genus Sahastata Benoit, 1968 is distributed in arid and semi-arid areas, from westernmost Sahara to India, and includes seven known species. Four of these are only known from one sex, including Sahastata nigra (Simon, 1897), the type species. Here we present the first description of a male of this species collected near the type locality in Muscat, Oman. Additionally, two new species are described: S. wunderlichi sp. nov. (♂♀, Morocco) and S. wesolowskae sp. nov. (♂♀, Oman). Sahastata infuscata (Kulczyński, 1901) is newly recorded from Kenya and Yemen and S. nigra is newly recorded from the United Arab Emirates. DNA barcodes are given for S. nigra and the two new species. We observed some details of the life cycle of three Sahastata species, including clutch size, time to maturation, and a biased sex ratio for individuals raised from egg sacs, indicating that only 20–25% of specimens reaching adulthood are males. We provide SEM images of spiders of this genus, some observations on the morphology of spinnerets and male palps, and a distribution map of the species included in the genus.